Daily Oxygen/O3 Treatment Reduces Muscular Fatigue and Improves Cardiac Performance in Rats Subjected to Prolonged High Intensity Physical Exercise. (21st July 2015) - Di Filippo, C.; Trotta, M. C.; Maisto, R.; Siniscalco, D.; Luongo, M.; Mascolo, L.; Alfano, R.; Accardo, M.; Rossi, C.; Ferraraccio, F.; D'Amico, M.
Abstract : Rats receiving daily intraperitoneal administration of O2 and running on a treadmill covered an average distance of 482.8 ± 21.8 m/week as calculated during 5-week observation. This distance was increased in rats receiving daily intraperitoneal administration of an oxygen/O3 mixture at a dose of 100; 150; and 300  μ g/kg with the maximum increase being +34.5% at 300  μ g/kg and still present after stopping the administration of oxygen/O3 . Oxygen/O3 decreased the mean arterial blood pressure (−13%), the heart rate (−6%), the gastrocnemius and cardiac hypertrophy, and fibrosis and reduced by 49% the left ventricular mass and relative wall thickness measurements. Systolic and diastolic functions were improved in exercised oxygen/O3 rats compared to O2 rats. Oxygen/O3 treatment led to higher MPI index starting from the dose of 150  μ g/kg (p < 0.05 ) and more effective (+14%) at a dose of 300  μ g/kg oxygen/O3 . Oxygen/O3 dose-dependently increased the expression of the antioxidant enzymes Mn-SOD and GPx1 and of eNOS compared to the exercised O2 rats. The same doses resulted in decrease of LDH levels, CPK, TnI, and nitrotyrosine concentration in the heart and gastrocnemius tissues, arguing a beneficial effect of the ozone molecule against the fatigue induced by a prolonged high intensity exercise.